ANALISIS MANAJEMEN STRES KERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Garmana, Deden Haria; Putri, Nurhayanti; Melianda, Risna; Sasmito, Nadya Salma; Salsabila, Rovi Aqila; Falah, Hamdan Nur (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to analyze the factors influencing employee performance at the Population and Civil Registration Office of Sumedang Regency, with a focus on the impact of work stress caused by low compensation, family problems, and lack of family support. The research uses a qualitative approach with in-depth interviews, observations, and documentation involving four key informants. The results show that low compensation significantly affects employee motivation, which in turn decreases work quality and exacerbates work-related stress. Additionally, family issues, such as tension in relationships with partners or children, and other familial responsibilities, also disrupt employees' concentration and productivity. The lack of family support in handling work-related burdens, both emotionally and practically, worsens the psychological pressure faced by employees. This study suggests several improvement measures, including enhancing organizational support in managing work stress, providing flexible working hours, and raising awareness of the importance of work-life balance